2018
DOI: 10.1002/joa3.12113
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of atrial fibrillation in patients with Brugada syndrome: A systematic review of the literature

Abstract: Supraventricular arrhythmias are common in Brugada syndrome (BS), and notoriously difficult to manage with medical therapy secondary to associated risks. Pulmonary vein isolation (PVI) is often utilized instead, but its outcomes in this population are not well‐known. We aim to provide a holistic evaluation of interventional treatment for Atrial fibrillation (AF) in the BS population. Electronic databases Medline, Embase, Cinahl, Cochrane, and Scopus were systematically searched for publications between 01/01/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A recent study suggested that ER was associated with lone AF ( 2 ). RFCA has also been reported to effectively maintain the sinus rhythm in Brugada syndrome patients with AF in several reports ( 11 , 12 ), however, the efficacy of RFCA for AF to maintain the sinus rhythm in patients with ERS has not yet been investigated. Further study will therefore be needed to validate the efficacy of RFCA for AF in patients with ERS.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study suggested that ER was associated with lone AF ( 2 ). RFCA has also been reported to effectively maintain the sinus rhythm in Brugada syndrome patients with AF in several reports ( 11 , 12 ), however, the efficacy of RFCA for AF to maintain the sinus rhythm in patients with ERS has not yet been investigated. Further study will therefore be needed to validate the efficacy of RFCA for AF in patients with ERS.…”
Section: Discussionmentioning
confidence: 99%
“…One more strategy to reduce inappropriate ICD therapies is the ablation procedure using either cryoablation technology or radiofrequency ablation for PVI. Rodriguez‐Manero et al 77 demonstrated in their review article that (a) freedom from AF recurrence in paroxysmal AF patients with BrS after PVI is high, (b) PVI reduces the need for AADs, and (c) ablation decreases the incidence of inappropriate ICD therapies caused by AF 77 …”
Section: Long‐term Management and Prognosismentioning
confidence: 99%
“…Rodriguez-Manero et al 77 demonstrated in their review article that (a) freedom from AF recurrence in paroxysmal AF patients with BrS after PVI is high, (b) PVI reduces the need for AADs, and (c) ablation decreases the incidence of inappropriate ICD therapies caused by AF. 77…”
mentioning
confidence: 99%